Morphological and physiological responses of the recalcitrant Euterpe edulis seeds to light, temperature and gibberellins - Roberto, G. G. [UNESP]; Habermann, G. [UNESP] (International Seed Testing Association, 2010)
Euterpe edulis is a key species of the Atlantic forest, but its seeds exhibit slow germination, which is a limiting factor for the successful establishment of the plant. This study assessed the capacity, time, rate, and synchrony of germination as a function of light vs. dark at different temperatures. At 25°C in the dark, which gave the optimum response, it was possible to note a time representing the beginning of the stationary phase (phase II) of the imbibition curve. We hypothesised that gibberellin (GA 3) and/or cytokinin (benzylaminopurine, BAP) applied at that imbibition time could improve germination performance, accelerating the germination of E. edulis seeds, enhancing propagation techniques used in palm tree nurseries, which provide palm plants for the re-composition of degraded fragments in the Atlantic forest. It was confirmed that GA3 at 50 mg. L-1 improved these responses. However, phase II could not be demonstrated as a better time to improve germination performance compared to the time immediately after sowing, since there were no embryo and/or endosperm anatomical differences between these times. This evidence supports published explanations for low germination performance of many palm fruits: primitive structure of the seed embryo and continuous development after fruit dispersion.